Property composition and other constructs to support identity in OWL - M. Colomb, Robert (Penerbit UTM Press, 2008)
This paper presents proposals for augmenting OWL Full with constructs necessary for supporting identity, an essential facility for ontologies governing interoperating information systems. These constructs include declaration that a property is one-to-one, a representation of the image of a property, and composition of properties. Using definitions from Category theory, property composition allows definition of Cartesian product without requiring that an individual have any internal structure. Category theory-style definitions and reasoning work entirely with properties, therefore are not affected by the open world semantics of OWL. The definitions permit representation of n-ary relations, association classes, parameterised families of properties and indexed families of classes.